A Review of Kidney Motion under Free, Deep and Forced-Shallow Breathing Conditions: Implications for Stereotactic Ablative Body Radiotherapy Treatment. (August 2014) - Pham, D.; Kron, T.; Foroudi, F.; Schneider, M.; Siva, S.
Motion management strategies are important during stereotactic ablative body radiotherapy for abdominal targets. The kidney is a mobile retroperitoneal organ that moves with respiration. A review of the literature was performed to investigate the reported degree of kidney motion associated with various breathing conditions. A structured search was performed using Medline from January 1970 to May 2013 for all publications describing cranial-caudal kidney motion. Relevance to radiotherapy practice was reviewed based on any breathing instructions and/or immobilization equipment that could affect breathing pattern. Studies were categorized under three types of breathing conditions: Forced-shallow, breath-hold/deep and free. A total of 25 publications were identified describing cranial-caudal kidney motion with a combined total of 415 participants. Three publications described forced-shallow breathing using prone positioning or abdominal compression plates. Prone positioning, compared to supine positioning, did little to minimise kidney motion, however use of compression plates can result in kidney motion of less than 5 mm. Eight publications described deep breathing/breath hold techniques that showed average kidney motion ranging between 10 mm-40 mm. Fifteen publications investigated kidney motion under free breathing with the majority reporting mean motion of less than 10 mm. Kidney movement of up to 8.1 mm in the anterior posterior direction and 6.2 mm laterally were reported with no indications that breathing technique can influence the extent of this motion. In summary, kidney movement is complex and consideration should be made to ensure that motion management strategies provide the desired radiotherapy benefit. There are limited publications on the effectiveness of abdominal compression on reducing kidney motion which warrant further investigation in this area.